The Role of Investigators in Dealing With Criminal Acts of Child Promiscuity - Jhon EJ Situmorang (Faculty of Law, Universitas Lampung, 2023)
This article aims to analyze the role of investigators in dealing with criminal acts of child promiscuity at the Lampung Regional Police and the inhibiting factors for the role of investigators in dealing with criminal acts of child promiscuity at the Lampung Regional Police. This type of research is a type of normative juridical research to examine and analyze cases handled by PPA Polda Lampung investigators in 2021 related to child promiscuity cases and to find out the role of investigators in dealing with child promiscuity crimes. The research findings show that the role of investigators in dealing with criminal acts of child promiscuity at the Lampung Regional Police is based on Law Number 8 of 1981 concerning the Criminal Procedure Code and the Police Law, which formulate cumulative criminal responsibility. The factors that impede the optimization of the investigator's role include the lack of several investigators and limited infrastructure.